Facing Climate Change: How to Manage the Arising New Crises? - Barthe-Delanoë, Anne-Marie; Fertier, Audrey; Chapuis, Kevin; Montarnal, Aurélie (Proceedings of the International ISCRAM Conference, 2025)
The increasing frequency and intensity of climate change-related disasters highlight the need to develop adaptive crisis management approaches. This paper explores the integration of R-IO Suite, a knowledge-based decision support system, with GAMA, a multi-agent simulation platform, to improve situational awareness and crisis response in a changing climate. This approach enables decision-makers and local communities to better understand, anticipate, and mitigate crisis impacts by combining real-time data modelling and predictive simulation. Although the proposed framework has been conceptually defined, its implementation and validation remain open key challenges. The French ANR-funded ATEsT project aims to overcome major technical obstacles— interoperability, semantic alignment, and temporal synchronisation—through concrete use cases. Future work will focus on implementing and testing this integration in realistic crisis scenarios, such as mega-fires and flash floods across different territories, to assess its effectiveness in improving decision-making processes and citizen engagement.